2015
DOI: 10.5607/en.2015.24.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mTOR Signaling in Brain Development

Abstract: mTOR is a serine/threonine kinase composed of multiple protein components. Intracellular signaling of mTOR complexes is involved in many of physiological functions including cell survival, proliferation and differentiation through the regulation of protein synthesis in multiple cell types. During brain development, mTOR-mediated signaling pathway plays a crucial role in the process of neuronal and glial differentiation and the maintenance of the stemness of neural stem cells. The abnormalities in the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 76 publications
2
86
0
Order By: Relevance
“…This remains in line with a previous report by other authors who also observed changes in mTOR level with age (Choi et al, 2016). The relatively low level of mTOR at birth in intubated groups might be related to the disruptive effect of prenatal stress and ethanol administration on the role of mTOR in the process of neuronal and glial differentiation during the third trimester (Lee, 2015). The mTOR level continued to be significantly lower in the fetal-ethanol pups throughout the whole brain spurt period when an intensive neurogenesis and cell growth still take place.…”
Section: Discussionsupporting
confidence: 92%
“…This remains in line with a previous report by other authors who also observed changes in mTOR level with age (Choi et al, 2016). The relatively low level of mTOR at birth in intubated groups might be related to the disruptive effect of prenatal stress and ethanol administration on the role of mTOR in the process of neuronal and glial differentiation during the third trimester (Lee, 2015). The mTOR level continued to be significantly lower in the fetal-ethanol pups throughout the whole brain spurt period when an intensive neurogenesis and cell growth still take place.…”
Section: Discussionsupporting
confidence: 92%
“…rapamycin" (mTOR) (4,40). These mutations in mice lead to a behavioral phenotype resembling autism (41), and targeting the mTOR pathway has been shown to reverse autism-like behavior (42,43).…”
mentioning
confidence: 99%
“…These cells release cytokines as a response to viral damage, promoting cell death and aberrant neurogenesis by NPCs (Bayless, Greenberg, Swigut, Wysocka, & Blish, 2016), the process responsible for populating the brain with neurons (Götz & Huttner, 2005). One of the key pathways in neurogenesis is the PI3K-Akt-mTOR axis that induces cellular differentiation, migration, and maturation (Lee, 2015;Wahane et al, 2014). After exposure to the two nonstructural ZIKV proteins, NS4A and NS4B, the PI3K-Akt-mTOR pathway was strongly suppressed, leading to upregulation of the autophagy and impairment of neurogenesis in fetal NSC (Liang et al, 2016).…”
Section: Experimental Findings That Clarified Zikv Pathology In Thementioning
confidence: 99%